2021
DOI: 10.1080/21655979.2021.1882134
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA DUXAP8 promotes the cell proliferation, migration, and invasion of papillary thyroid carcinoma via miR-223-3p mediated regulation of CXCR4

Abstract: 2021) Long non-coding RNA DUXAP8 promotes the cell proliferation, migration, and invasion of papillary thyroid carcinoma via miR-223-3p mediated regulation of CXCR4,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In myeloid cells, CXCR4-mediated signals inhibit natural killer (NK) cell-mediated tumor immune surveillance and consequently promote tumor expansion [38]. Recently, Liu et al reported that DUXAP8, a long noncoding RNA (lncRNA), plays an active role in activating cell proliferation, migration, and invasion of papillary thyroid carcinoma through regulating CXCR4 mediated by miR-223-3p [39]. In another study, Zou et al found that CXCR4 was overexpressed in the TME of soft tissue sarcomas [40].…”
Section: Discussionmentioning
confidence: 99%
“…In myeloid cells, CXCR4-mediated signals inhibit natural killer (NK) cell-mediated tumor immune surveillance and consequently promote tumor expansion [38]. Recently, Liu et al reported that DUXAP8, a long noncoding RNA (lncRNA), plays an active role in activating cell proliferation, migration, and invasion of papillary thyroid carcinoma through regulating CXCR4 mediated by miR-223-3p [39]. In another study, Zou et al found that CXCR4 was overexpressed in the TME of soft tissue sarcomas [40].…”
Section: Discussionmentioning
confidence: 99%
“…Transwell assay was used for assessing the migratory and invasive abilities of transfected HCC cells [ 28 ]. The transwell chambers (pore size, 8 μm) were precoated with Matrigel (BD Biosciences, NJ, USA) for invasion assay and were not precoated with Matrigel for migration assay.…”
Section: Methodsmentioning
confidence: 99%
“…Cell migration ability was evaluated using a wound healing assay [ 18 ]. T24 and 5637 (2 x 10 6 ) cells were seeded into 6-well plates.…”
Section: Methodsmentioning
confidence: 99%